Appointment of councillors: a review on local government act 1976 / Syafiq Affandy Hasan … [et al.] - Hasan, Syafiq Affandy; Denci, Mirnawati; Saparudin, Nurul Syazwani; Mohd Shafee, Norshazlida (Faculty of Law, 2013)
The local government election was suspended on 1965 due to the Indonesia- Malaysia confrontation in 1964 and it has never been reintroduced since then. The Local Government Election 1965 was changed to Local Government Act 1971. Under the Act, the state government appoints local government members. This research will focus on the appointment of councilors. Some people argued on the reviving of the local government elections to sustain their right in electing their representatives. Therefore, this research aims to analyze the problems with the current system of appointment of councilors. This research also includes a few recommendations that may be taken into consideration to curb the issues at hand.